Ductal Carcinoma In Situ (DCIS) Diagnosed by MRI-Guided Biopsy among BRCA1/BRCA2 Mutation Carriers. (27th October 2022) - Faermann, Renata; Friedman, Eitan; Kaidar-Person, Orit; Weidenfeld, Jonathan; Brodsky, Malka; Shalmon, Anat; Halshtok Neiman, Osnat; Gotlieb, Michael; Yagil, Yael; Samoocha, David; Madorsky Feldman, Dana; Sklair-Levy, Miri
Abstract : Background . While BRCA1/BRCA2 pathogenic sequence variants (PSVs) clearly confer an increased risk for invasive breast cancer, the extent to which these mutant alleles increase DCIS risk is less clear. Objective . To assess the rate of detection over a 5-year period, and MRI imaging features of pure noncalcified DCIS in a cohort of Israeli BRCA1/BRCA2 PSV carriers attending a high-risk clinic from 2015 to 2020. Materials and Methods . All female BRCA1/BRCA2 PSV-carriers followed at the Meirav High-risk clinic from 2015 to 2020 were eligible if they underwent semiannual breast imaging (MRI/mammography) and MRI-guided biopsy-proven pure DCIS. Clinical data, pathology information, and imaging characteristics were retrieved from the computerized archiving system. Results . 18/121 (15.2%) participating BRCA1 PSV carriers and 8/81 (10.1%) BRCA2 PSV-carriers who underwent MRI-guided biopsy were diagnosed with DCIS. The median age of BRCA1 carriers and BRCA2 carriers was 49.8 years and 60.6 years, respectively (p = 0.55 ). Negative estrogen-receptor tumors were diagnosed in 13/18 (72%) BRCA1 and 2/8 (25%) BRCA2 PSV carriers (p < 0.05 ). Thirteen (13/18–72%) BRCA1 carriers had intermediate to high-grade or high-grade DCIS compared with 4/8 (50%) of BRCA2 carriers (p = 0.03 ). Over the 5-year study period, 29/1100 (2.6%) BRCA1/BRCA2 PSV carriers were diagnosed with DCIS seen on MRI only. Conclusion . MRI-detected noncalcified DCIS is more frequent in BRCA1 PSV carriers compared with BRCA2 carriers, unlike the BRCA2 predominance in mammography-detected calcified DCIS. BRCA1 -related DCIS is diagnosed earlier, more likely to be estrogen receptor-negative and of higher grade compared with BRCA2 -related DCIS. Future prospective studies should validate these results and assess the actual impact they might have on clinical management of BRCA PSV carriers.